The Relationship Parity and Family Support with Psychological Adaptation of The Postpartum Period at the Jawiriyah Midwife Maternity Clinic in Banda Aceh City - Irma Afriana; Yusnaini Yusnaini; Kartinazahri Kartinazahri; Gustiana Gustiana (Midwifery and Nursing Research, 2023)
Background: If the mother is unable to adapt psychologically in the taking in phase, the taking hold phase, and the letting go phase, the mother will experience impaired psychological adaptation during the postpartum period such as postpartum blues, or postpartum depression, postpartum psychosis or postpartum psychiatric. The ability to listen and provide adequate time is an invaluable support for the mother. Research Objectives : To determine the relationship between parity and family support with psychological adaptation during the postpartum period at the Jawiriyah Midwife Maternity Clinic, Banda Aceh City. Methods: This research is analytic in nature with a cross sectional approach. The sample in this study were mothers who gave birth at the Jawiriyah midwife maternity clinic. Sampling using Accidental sampling technique and obtained as many as 30 respondents. Processing data using chi-square test. Results: The results of the chi-square test found that there was a relationship between parity (p-value = 0.018), and family support (p-value = 0.009) with psychological adaptation during the postpartum period at the Jawiriyah Midwife Maternity Clinic, Banda Aceh City. Conclusion: There is a relationship between parity and family support with psychological adaptation during the postpartum period. Suggestions for research sites are expected to be input in providing health education for postpartum mothers about psychological adaptation and collaborating with the Public health center in providing counseling regarding psychological adaptation and teaching how to deal with psychological problems that arise during the postpartum period.